Yolk color and lipid oxidation of the eggs of commercial white layers fed diets supplemented with vegetable oils - Faitarone, Ana Beatriz Garcia [UNESP] (2016)
The objective of this study was to evaluate the influence of the supplementation of vegetable oils rich in polyunsaturated fatty acids to the diet of Leghorn layers on yolk color and on yolk lipid oxidation of eggs stored at room temperature for 10 days. Sixty eggs laid by commercial white layers (Lohmann LSL) fed diets supplemented with different vegetable oils were used. Hens were fed one of the following treatment diets: conventional diet with no oil inclusion (T1); T1 diet with 2.5% linseed oil inclusion (T2); T1 diet with 2.5% canola oil (T3); T1 diet with 2.5% soybean oil (T4); T1 with 5.0% linseed oil (T5); T1 diet with 5.0% canola oil (T6); T1 diet with 5.0% soybean oil (T7); T1 diet with 2.5% linseed oil + 2.5% soybean oil (T8); T1 diet with 2.5% canola oil + 2.5% soybean oil (T9); and T1 diet with 2.5% linseed oil + 2.5% canola oil (T10). Eggs were evaluated as to yolk lipid peroxidation (TBARS values) and yolk color, as determined by colorimetry and subjective sensorial analysis. Data were submitted to analysis of variance and means were compared by the test of Tukey at 5% significance level. It was concluded that the inclusion of vegetable oils in commercial white layer diets does not significantly change egg yolk pigmentation, as colorimetrically evaluated. However, when subjectively assessed, the yolks of the eggs laid by hens fed diets supplemented with vegetable oils tend to be paler. The yolks of the eggs laid by layers fed diets containing sources of polyunsaturated fatty acids presented high lipid oxidation, particularly when compared with those derived from layers fed the diet with no oil supplementation.